Two new species of loaches from the Irrawaddy River basin, Chin State, Myanmar (Teleostei: Cypriniformes: Nemacheilidae) - Chen, Meng-Fang; Myint, Khin Mar; Chu, Ling; Chen, Xiao-Yong (Zootaxa, 2020)
Schistura falamensis, a new species of nemacheilid loach, is described from the main channel of the Manipur River in the Irrawaddy River basin, Chin State, western Myanmar. It differs from other congeners of the genus Schistura by a combination of the following characters: 5–8 vertical bars on body; indistinct bars in front of dorsal-fin origin; bars on posterior part of body regular, twice as wide as interspace; black caudal basal bar dissociated, short, not reaching ventral extremity; males with suborbital flap; lateral line complete; and processus dentiformis weak. Schistura altuscauda is a new species described from the Htin stream, Mindat Town, Chin State, Myanmar. It can be distinguished from other congeners by a combination of the following characters: high caudal peduncle (14.0–20.3% SL), strong processus dentiformis on upper jaw; 7–19 bars on flank of body, bars in front of dorsal fin obviously thinner than those behind, sometimes fused in front of dorsal fin; lateral line complete; males with prominent suborbital flap; and pelvic lobe present.